Lithium recovery from mixed spent LFP-NMC batteries through atmospheric water leaching - Indra Perdana; Doni Riski Aprilianto; Farika Asna Fadillah; Riskal Fadli; Himawan Tri Bayu Murti Petrus; Widi Astuti; Muhammad Akhsin Muflikhun; Hanida Nilasary; Haryo Satriya Oktaviano; Ferry Fathoni; Edo Raihan; Soraya Ulfa Muzayanha (Scientific Reports)
Abstract Selective lithium recovery from a mixture of LFP-NMC spent lithium batteries presents significant challenges due to differing structures and elemental compositions of the batteries. These differences necessitate a distinct recycling pathway for each, complicating the process for the mixture. This study explored a carbothermal reduction approach combined with water leaching under atmospheric conditions to achieve a selective lithium recovery. For individual NMC black mass, at the optimal carbothermal conditions (950 °C, 15 °C/min, 2 h), lithium recovery of 95.7 ± 0.31% with 100% selectivity could be achieved. However, when the black mass was mixed with that of LFP in a 50:50 ratio, the recovery dropped to 9.78 ± 0.44%. Solid-state reactions during carbothermal process resulted in the formation of highly insoluble Li3PO4, and Fe-Ni-Co/Ni-Co alloys, which hinder lithium dissolution. To address these challenges, Na2CO3 was introduced as an additive to suppress Li3PO4. The addition of Na2CO3 to the 50:50 ratio of LFP-NMC black mass, increased lithium recovery to 59.47% with 100% selectivity. This enhancement was due to the stabilization of lithium as Li2CO3, a water-soluble compound. The results demonstrated that addition of Na2CO3 is a promising strategy for improving lithium recovery from mixed LFP-NMC batteries, providing a potential pathway for a more efficient recycling process.